2021
DOI: 10.1108/jm2-06-2020-0162
|View full text |Cite
|
Sign up to set email alerts
|

A robust possibilistic programming model for production-routing problem in a three-echelon supply chain

Abstract: Purpose This paper aims to provide an integrated production-routing model in a three-echelon supply chain containing a two-layer transportation system to minimize the total costs of production, transportation, inventory holding and expired drugs treatment. In the proposed problem, some specifications such as multisite manufacturing, simultaneous pickup and delivery and uncertainty in parameters are considered. Design/methodology/approach At first, a mathematical model has been proposed for the problem. Then,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…We have identified that the application of AI and ML can help to reduce the bullwhip effect (BWE) in the supply chain and possible solutions to better production decisions (Beheshtinia et al , 2021). In line with our claim, Singh and Challa (2016) also, confirmed that the use of integrated forecasting using AI techniques can reduce the BWE in a supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified that the application of AI and ML can help to reduce the bullwhip effect (BWE) in the supply chain and possible solutions to better production decisions (Beheshtinia et al , 2021). In line with our claim, Singh and Challa (2016) also, confirmed that the use of integrated forecasting using AI techniques can reduce the BWE in a supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…Beheshtinia et al 23 integrated production and routing problems in a pharmaceutical supply chain to minimize total costs of production, transportation, inventory holding, and expired drug treatment. After presenting the mathematical model of the problem, they proposed a possibilistic model and a robust possibilistic model to consider the uncertainty in the problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because the study is concerned with the influence of perishable commodities age on ultimate consumer demand, all three echelons are taken into account in the optimization, and numerical findings are provided in the form of large-scale problems utilizing the CPLEX solver, PSO algorithms and biogeographical based optimization. To reduce overall expenses for manufacturing, transportation, inventory storage and expired medicine treatment, Beheshtinia et al (2021) presented a three-echelon location routing model with a two-layer transportation system. Some criteria, such as multisite production, simultaneous delivery and pickup, and parameter uncertainty, are taken into account in the suggested problem.…”
Section: Location and Routing Problemsmentioning
confidence: 99%